Implementasi dan Analisis Quality of Service (QoS) pada OpenMeetings dengan Virtual Private Network (VPN) - Amiza, Ibel Dwi; Lindawati, Lindawati; Soim, Sopian (Universitas Halu Oleo, 2020)
AbstractÂ â€”Â Video Conference is a communication service that can be used to bring together two users (client) or more. Video conferencing can be used for a variety of activities that require communication in real-time without having to come face to face directly. One open-source that can be utilized as a means of communicating is OpenMeetings. OpenMeetings uses IP and in the same network as a means of conducting video conferencing between clients. But if a client is not in the same network, it can utilize the Virtual Private Network (VPN) technology. The VPN can be remote by using a MikroTik router. The Video conferencing service requires fairly high and stable connectivity. Quality of Service (QoS) can be used whether the network is eligible for video conferencing. The QoS parameters used are throughput and packet loss. The QoS test can be done using Wireshark.